2021
DOI: 10.3389/fonc.2021.703143
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Smoking History on Response to Immunotherapy in Non-Small-Cell Lung Cancer: A Systematic Review and Meta-Analysis

Abstract: ObjectivesTo evaluate the impact of smoking history on the clinical benefit of immunotherapy in patients with non-small cell lung cancer (NSCLC).MethodsTwenty-three randomized clinical trials and seven real-world studies were included in this meta-analysis. Hazard ratios (HRs) and 95% confidence intervals (CIs) for overall survival (OS) and progression-free survival (PFS) and odds ratios for the overall response rate (ORR) were extracted. A fixed-effects or random-effects model was applied to obtain pooled est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 61 publications
(44 reference statements)
4
32
0
Order By: Relevance
“…A recent meta-analysis by Dai et al [ 100 ] found that ICI monotherapy and dual ICIs improved survival in ever smokers but not never smokers, regardless of PD-L1, and that the addition of chemotherapy was able to improve survival for both groups. Several real-world studies and analyses further support these observed associations [ 101 , 102 , 103 ].…”
Section: Future Directions To Understanding Tobacco Use and Ici Outcomesmentioning
confidence: 70%
“…A recent meta-analysis by Dai et al [ 100 ] found that ICI monotherapy and dual ICIs improved survival in ever smokers but not never smokers, regardless of PD-L1, and that the addition of chemotherapy was able to improve survival for both groups. Several real-world studies and analyses further support these observed associations [ 101 , 102 , 103 ].…”
Section: Future Directions To Understanding Tobacco Use and Ici Outcomesmentioning
confidence: 70%
“…We also found that smoking status was an independent factor for OS. Patients who have smoked might have more mutant antigens causing lung cancer, which has been revealed in previous studies of immunotherapy ( 30 , 31 ). Subgroup analysis of immunotherapy in patients with EGFR/ALK-negative NSCLC with SMS-low showed significantly better PFS than those with SMS-high.…”
Section: Discussionmentioning
confidence: 71%
“…On the one hand, it is well-known that smoking is of great importance in the morbidity and mortality of lung cancer ( Loeb et al, 1984 ; Jung et al, 2016 ). On the other hand, the impact of smoking on treatment decisions is controversial and is recently being widely investigated ( Lin et al, 2018 ; Li et al, 2020 ; Xiao et al, 2020 ; Chen et al, 2021 ; Zhao et al, 2021 ). To our knowledge, the comprehensive and systematic analysis of the relationship between smoking status and first-line treatment efficacy of advanced ALK-positive NSCLC has not been reported yet.…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco use impairs the treatment efficacy of lung cancer and shortens patients’ survival as smoking tobacco directly influences response to anti-tumor drugs by affecting drugs metabolism ( Gemine and Lewis, 2016 ). On the contrary, immunotherapy performs better in NSCLC patients with a smoking history ( Li et al, 2020 ; Nie et al, 2020 ; Zhao et al, 2021 ). Notably, both studies in the Asian-only subgroup used alectinib, despite dosage differences, which may suggest the excellent efficacy of alectinib in smokers, while the experimental ALK-TKIs in another group dramatically varied in multiracial studies.…”
Section: Discussionmentioning
confidence: 99%